Applying Methods of Estimating Indefiniteness Conditions in the Context of Ensuring Economic Safety of Regions - ORLOVA, Anna Viktorovna; LYSHCHIKOVA, Julia Vladimirovna (Journal of Advanced Research in Law and Economics, 2017)
High level of indefiniteness and the crisis nature of the current economic system cause external and internal threats that have an essential impact on the social and economic development of regions. It makes people pay close attention to the issues related to servicing and managing their economic safety. The goal of this research is to stipulate and develop tools on estimating the comprehensive territorial force. The authors formulated a system of particular indicators of the expert estimation of the territory development under conditions of indefiniteness in the context of the process related to taking decisions on ensuring their economic safety. The content of the comprehensive territorial force and the parameters of the process related to the social and economic state of regions were defined during the research. The results of the research can be used to reveal peculiarities of the territorial force and to define areas of building mechanisms on ensuring economic safety of regions.